Diarrhea treatment center (DTC) based diarrheal disease surveillance in settlements in the wake of the mass influx of forcibly displaced Myanmar national (FDMN) in Cox's Bazar, Bangladesh, 2018. - Abu S G Faruque (Public Library of Science (PLoS), 2021)
Background In August 2017, after a large influx of forcibly displaced Myanmar nationals (FDMN) in Cox's Bazar, Bangladesh diarrhea treatment centers (DTCs) were deployed. This study aims to report the clinical, epidemiological, and laboratory characteristics of the hospitalized patients. Methods The study followed cross-sectional design. In total 1792 individuals were studied. Other than data, a single, stool specimen was subjected to one step rapid visual diagnostic test for Vibrio cholerae. The provisionally diagnosed specimens of cholera cases were inoculated into Cary-Blair Transport Medium; then sent to the laboratory of icddr,b in Dhaka to isolate the colony as well as perform antibiotic susceptibility tests. Data were analyzed by STATA and analyses included descriptive as well as analytic methods. Results Of the total 1792 admissions in 5 DTCs, 729 (41%) were from FDMN settlements; children <5 years contributed the most (n = 981; 55%). Forty percent (n = 716) were aged 15 years and above, and females were predominant (n = 453; 63%). Twenty-eight percent (n = 502) sought treatment within 24h of the onset of diarrhea. FDMN admissions within 24h were low compared to host hospitalization (n = 172, 24% vs. n = 330, 31%; p<0.001). Seventy-two percent (n = 1295) had watery diarrhea; more common among host population than FDMN (n = 802; 75% vs. n = 493; 68%; p<0.001). Forty-four percent admissions (n = 796) had some or severe dehydration, the later was common in FDMN (n = 46; 6% vs. n = 36; 3%, p = 0.005). FDMN often used public taps (n = 263; 36%), deep tube-well (n = 243; 33%), and shallow tube well (n = 188; 26%) as the source of drinking water. Nearly 96% (n = 698) of the admitted FDMN used pit latrines as opposed to 79% (n = 842) from the host community (p<0.001). FDMN children were often malnourished. None of the FDMN reported cholera. Conclusion No diarrhea outbreak was detected, but preparedness for surges and response readiness are warranted in this emergency and crisis setting.